Efficient production of 1,3-propanediol from crude glycerol by repeated fed-batch fermentation strategy of a lactate and 2,3-butanediol deficient mutant of Klebsiella pneumoniae - Oh, Baek-Rock (Microb Cell Fact, 2018)
BACKGROUND: 1,3-Propanediol (1,3-PDO) is important building blocks for the bio-based chemical industry, Klebsiella pneumoniae can be an attractive candidate for their production. However, 1,3-PDO production is high but productivity is generally low by K. pneumoniae. In this study, repeated fed-batch cultivation by a lactate and 2,3-butanediol (2,3-BDO) deficient mutant of K. pneumoniae were investigated for efficient 1,3-PDO production from industrial by-products such as crude glycerol. RESULTS: First, optimal conditions for repeated fed-batch fermentation of a ΔldhA mutant defective for lactate formation due to deletion of the lactate dehydrogenase gene (ldhA) were determined. Maximal 1,3-PDO production level and productivity obtained by repeated fed-batch fermentation under optimized conditions were 81.1 g/L and 3.38 g/L/h, respectively, and these values were successfully maintained for five cycles of fermentation without any loss of fermentation capacity. This results were much higher than that of the normal fed-batch fermentation. The levels of 2,3-BDO, which is a major by-product, reaching up to ~ 50% of the level of 1,3-PDO, were reduced using a mutant strain [Δ(ldhA als)] containing an additional mutation in the biosynthetic pathway of 2,3-BDO (deletion of the acetolactate synthase gene). The levels of 2,3-BDO were reduced to about 20% of 1,3-PDO levels by repeated fed-batch fermentation of Δ(ldhA als), although maximal 1,3-PDO production and productivity also decreased owing to a defect in the growth of the 2,3-BDO-defective mutant strain. CONCLUSION: This repeated fed-batch fermentation may be useful for reducing the cost of 1,3-PDO production and may be promising industrialization prospect for the 1,3-PDO production.